2016
DOI: 10.1017/s0305000915000768
|View full text |Cite
|
Sign up to set email alerts
|

How do language-specific characteristics affect the acquisition of different relative clause types? Evidence from Finnish

Abstract: Kirjavainen, M., Kidd, E. and Lieven, E. (2017) Disclaimer UWE has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material. UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited. UWE makes no representation that the use of the materials will not infringe any patent, copyright, trademark or other property… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
6
11
0
Order By: Relevance
“…When we restrict our analysis to true RCs only, we see the opposite effect: object RCs are more frequent than subject RCs (95 vs. 26). Consistent with similar analyses in other languages (Diessel, 2009;Kidd et al, 2007;Kirjavainen et al, 2017), the majority of the object RCs had inanimate head nouns (90 inanimate vs. 5 animate), whereas animacy in subject RC head nouns was more balanced (16 inanimate vs. 10 animate).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When we restrict our analysis to true RCs only, we see the opposite effect: object RCs are more frequent than subject RCs (95 vs. 26). Consistent with similar analyses in other languages (Diessel, 2009;Kidd et al, 2007;Kirjavainen et al, 2017), the majority of the object RCs had inanimate head nouns (90 inanimate vs. 5 animate), whereas animacy in subject RC head nouns was more balanced (16 inanimate vs. 10 animate).…”
Section: Discussionsupporting
confidence: 87%
“…However, what is not entirely clear is whether it holds crosslinguistically. While the subject advantage is robust in commonly studied languages, such as English (Kidd & Bavin, 2002), German (Brandt, Kidd, Lieven, & Tomasello, 2009), and Italian (Adani, 2011), in addition to Hebrew (Arnon, 2010;Friedman, Belletti, & Rizzi, 2009), several counterexamples of an object advantage or null effects have been reported in morphologically rich languages such as Basque (Carreiras, Duñabeitia, Vergara, de la Cruz-Pavía, & Laka, 2010;Gutierrez-Mangado, 2011), Finnish (Kirjavainen, Kidd, & Lieven, 2017;Kirjavainen & Lieven, 2011), Japanese (Ozeki & Shirai, 2007a;Suzuki, 2011), and Quechua (Courtney, 2006(Courtney, , 2011. In this study we focus on one language that has produced notably inconsistent results across studies but which is a particularly important language for deciding between two classes of theories: Mandarin.…”
mentioning
confidence: 99%
“…For children, this advantage was demonstrated as more accurate comprehension (Hebrew: Friedmann & Novogrodsky, 2004), production (Danish: Jensen de López, Sundahl Olsen, & Chondrogianni, 2014), and repetition (English and German: Diessel & Tomasello, 2005) of subject relative clauses. However, studies conducted in Basque (Gutierrez-Mangado, 2011), Finnish (Kirjavainen et al, 2017), and Japanese (Suzuki, 2011) revealed that this advantage is not universal and cannot be accounted for by syntactic accounts only (such as the Noun Phrase Accessibility Hierarchy (Keenan & Comrie, 1977) and the Linear Distance Hypothesis (Gibson, 1998)). That not only syntactic but also semantic features of relative clauses affect their processing has been shown by studies finding that both adult and child speakers find object relatives with inanimate head nouns and personal pronominal subjects (e.g., the building that I saw) much easier to process than the ones with animate head nouns and lexical subjects (e.g., the bird that the cat saw) (Arnon, 2010;Kidd, Brandt, Lieven, & Tomasello, 2007;Mak, Vonk, & Schriefers, 2006;Traxler, Morris, & Seely, 2002).…”
Section: Acquisition Of Relative Clausesmentioning
confidence: 99%
“…Young children's acquisition and use of relative clauses has been investigated in typologically diverse languages (e.g., Arnon, 2010;Brandt, Diessel, & Tomasello, 2008;Courtney, 2006;Hamburger & Crain, 1982;Ozeki & Shirai, 2010). The order of acquisition and frequency of different types of relative clauses in child speech, and their functions in child-directed interactions differ across languages (e.g., Chen & Shirai, 2015;Kirjavainen, Kidd, & Lieven, 2017;Ozeki & Shirai, 2007). Here we investigate the acquisition and use of relative clauses by Turkish-speaking children within a large age range (0;8 to 5;4) through examining their spontaneous conversations with their caregivers and peers.…”
mentioning
confidence: 99%
“…Relative clauses (RCs) are a commonly studied structure in both adult and child psycholinguistic research. It is a well-known phenomenon that, at least for most European languages (Kirjavainen, Kidd, & Lieven, 2016), subject RCs such as (1) are easier to process for both children and adults than object RCs such as (2) (e.g., Diessel & Tomasello, 2005;Gibson, 1998).…”
Section: Relative-clause Processing and Acquisitionmentioning
confidence: 99%